The Operational Development of Student Care and Support System for Teachers at Nuaklongprachabumrung School in Krabi Province - Pongtongmueng, Sarayuth; Sangkhaosuthirak, Sathaporn; Jaroensuk, Bunjong (Rajapark Journal, 2021)
The purposes of this research were 1. To study the current conditions and the needs of the development of the students’ care and support operation system. 2. To develop the operations in the students’ care and support system for teachers. 3. To assess the result of the operation for teachers in the student care and support system as follows. This study was conducted by the action research method, including four steps: planning, action, observation, and reflection, and it took two cycles. The population involved 52 participants, including an advisor teacher in each class at Nuaklongprachabumrung School. Applying the form of the need and current condition, the cognition test, the skill assessment, the questionnaire, and data were analyzed by percentage, standard deviation, and t-test. The research findings were as follows. 1. The current state and requirements for the development of a student care and support operation system for teachers at Nuaklongprachabumrung School, Krabi province, in total, were high, and the needs for operational development were at the highest level. 2. The operational development of the student care and support system for teachers after the workshop was higher at a statistical significance level of .05. 3. The assessment of the operational development of the students’ care and support system. The overall questionnaire ranking from high to low, the satisfaction with the operational development of the students’ care and support system was at the highest level.